2004
DOI: 10.1074/jbc.m310719200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of DnaE, the Second Replicative DNA Polymerase from Bacillus subtilis, in DNA Mutagenesis

Abstract: In a large group of organisms including low G ؉ C bacteria and eukaryotic cells, DNA synthesis at the replication fork strictly requires two distinct replicative DNA polymerases. These are designated pol C and DnaE in Bacillus subtilis. We recently proposed that DnaE might be preferentially involved in lagging strand synthesis, whereas pol C would mainly carry out leading strand synthesis. The biochemical analysis of DnaE reported here is consistent with its postulated function, as it is a highly potent enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
82
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 74 publications
9
82
1
Order By: Relevance
“…While this review was going to press, Le Chatelier et al (2004) provided further evidence for the asymmetric nature of replication forks in B. subtilis. Massey et al (2004) show that the previously proposed RAG polarized motifs (Capiaux et al, 2001;Lobry & Louarn, 2003) are not implicated in the mobilization of DNA by FtsZ.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…While this review was going to press, Le Chatelier et al (2004) provided further evidence for the asymmetric nature of replication forks in B. subtilis. Massey et al (2004) show that the previously proposed RAG polarized motifs (Capiaux et al, 2001;Lobry & Louarn, 2003) are not implicated in the mobilization of DNA by FtsZ.…”
Section: Note Added In Proofmentioning
confidence: 99%
“…Mtb contains two DnaE-type polymerases; the other, DnaE1, provides essential, high-fidelity replicative polymerase function (1). However, the basis for the functional specialization of the DnaE subunits remains unclear (2,3). Although structural determinants such as active-site architecture contribute significantly to inherent fidelity, it is possible that differential interactions with other DNA metabolic proteins modulate polymerase function.…”
mentioning
confidence: 99%
“…In vitro reconstitution of the B. subtilis replisome has demonstrated that PolC (163 kD) is responsible for all leading strand synthesis as well as most lagging strand synthesis, whereas the more error prone and much slower DNA replicase DnaE (25 nt/s for DnaE compared to~500 nt/s for PolC) plays a crucial role in initiating lagging strand synthesis (10,16). DnaE is important for extending the lagging strand RNA primer before handing off to PolC, which then completes replication of the Okazaki fragment (10).…”
Section: Introductionmentioning
confidence: 99%